Pengembangan Bahan Ajar Berbentuk Booklet Materi Masuk dan Berkembangnya Islam ke Indonesia Siswa Kelas X SMA Negeri Tugumulyo - Mita Anggelia (Yupa: Historical Studies Journal, 2021)
This study aims to develop a history booklet about the entry and development of Islam in Indonesia for class X SMA Negeri Tugumulyo according to the 2013 curriculum. This research is development research using a 4-D model which consists of four stages, namely: definition, design, development, and dissemination. Based on the results of the analysis of the assessment by three experts, namely linguists, media experts, and material experts, it shows that the material history booklet of the entry and development of Islam into Indonesia fulfills the valid category with an average score of 3,21. While the results of the analysis of the student assessment sheet consisting of 31 people, it was found that the history booklet of material entry and development of Islam into Indonesia fulfilled the practical category with an average score of 3,60. The result of the t-hitung is 7,472, the significance level is a=0,05 with the degrees of freedom (dk/df) 31, the t-tabel is 1,697 with a significance of 0,000, which means it is smaller than 0,05, there is a significant relationship, meaning that the history booklet material for the entry and development of Islam into Indonesia is valid, practical, and effective.